Mapping species richness of plant families in European vegetation. (18th May 2021) - Večeřa, Martin; Axmanová, Irena; Padullés Cubino, Josep; Lososová, Zdeňka; Divíšek, Jan; Knollová, Ilona; Aćić, Svetlana; Biurrun, Idoia; Boch, Steffen; Bonari, Gianmaria; Campos, Juan Antonio; Čarni, Andraž; et al.
Abstract: Aims: Biodiversity is traditionally studied mostly at the species level, but biogeographical and macroecological studies at higher taxonomic levels can provide valuable insights into the evolutionary processes at large spatial scales. Our aim was to assess the representation of vascular plant families within different vegetation formations across Europe. Location: Europe. Methods: We used a data set of 816, 005 vegetation plots from the European Vegetation Archive (EVA). For each plot, we calculated the relative species richness of each plant family as the number of species belonging to that family divided by the total number of species. We mapped the relative species richness, averaged across all plots in 50 km × 50 km grid cells, for each family and broad habitat groups: forests, grasslands, scrub and wetlands. We also calculated the absolute species richness and the Shannon diversity index for each family. Results: We produced 522 maps of mean relative species richness for a total of 152 vascular plant families occurring in forests, grasslands, scrub and wetlands. We found distinct spatial patterns for many combinations of families and habitat groups. The resulting series of 522 maps is freely available, both as images and GIS layers. Conclusions: The distinct spatial patterns revealed in the maps suggest that the relative species richness of plant families at the community level reflects the evolutionary history of individual families. We believe that the maps and associated data can inspire further biogeographical and macroecological studies and strengthen the ongoing integration of phylogenetic, functional and taxonomic diversity concepts. Abstract : We assessed the relative species richness of vascular plant families within forests, grasslands, scrub and wetlands across Europe based on the European Vegetation Archive data. In many cases, we found distinct spatial patterns in the representation of families within different habitats, which may reflect the biogeographical and evolutionary history of individual families. ​